تنفيذ التقييم الحقيق الربنامج المكثف لتعليم ي ف اللغة العربية جامعة موالنا مالك إبراهيم اإلسالمية الحكومية ماالنج - عيني, دليلا; محمودة, امي; ميمون, اغوس; حسنية, نور (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
The purpose of the study is to determine the authentic assessment of speaking skill special Arabic language development program learning at State Islamic University Maulana Malik Ibrahim Malang. This research uses a quasi-qualitative approach with a case study method. This research was carried out at the special Arabic language development program (PKPBA) at UIN Maulana Malik Ibrahim Malang. The source of data in this study is informants selected by purposive sampling, namely the head of the language center, the head of PKPBA, and several lecturers at PKPBA. Data collection is carried out by several techniques, namely: (a) observation; (b) interviews; and (c) documentation. The results of the study in this study show the application of authentic assessment to speaking skill learning at PKPBA UIN Malang. Specifically, by using attitude assessment Attitude assessment is carried out through observation, self assessment, assessment between friends, and journals. Knowledge assessment is conducted through written tests, oral tests, and assignments. Skills assessment is carried out through performance appraisals and portfolio appraisals.